Analisis Yuridis Penistaan Agama di Media Sosial Menurut Hak Asasi Manusia - Aime Sumolangi; Emma V. T. Senewe; Caecilia J. J. Waha (Journal on Education, 2023)
Freedom of expression through social media is one of the rights guaranteed in international human rights agreements. Nonetheless, this freedom can create conflict if freedom of expression is used to insult or harass certain groups or religions. This thesis will examine the juridical analysis of religious blasphemy on social media according to human rights. The criminalization of blasphemy in Indonesia is primarily based on two legal documents. Article 156(a) of the Criminal Code criminalizes the expression "enmity, hatred or contempt for" a religious group. A presidential decree enacted in 1965 (PD No. 1/PNPS/1965) broadened the definition of blasphemy to prohibit “distorted interpretations” of religious teachings. Individuals convicted of blasphemy charges can be sentenced to a maximum of four years in prison under the Criminal Code and five years in prison under a presidential decree. This research is a type of library research. The data sources used in this study are secondary data in the form of books, journals, research results and other written sources. Data collection techniques were carried out using the documentation method and review of the written sources. The journals used in this study are journals published in the last 5 years, namely the period 2018-2022. The results of the study show that the human rights law against religious blasphemy in social media in Indonesia is basically contrary to universal human rights recognized in international conventions on freedom of expression. The existing human rights legal arrangements in Indonesia also do not yet cover in detail the limits of freedom of expression on social media which are considered to be religious blasphemy.